PROBLEM-BASED LEARNING IN TEACHING WRITING APPLICATION LETTER TO THE TWELFTH GRADERS OF SMKN 6 SURABAYA (RETAIN, 2016)
PROBLEM-BASED LEARNING IN TEACHING WRITING APPLICATION LETTER TO THE TWELFTH GRADERS OF SMKN 6 SURABAYA Devi Indriani English Education Department, Language and Art Faculty, Surabaya State University. deviindriani@mhs.unesa.ac.id Ririn Pusparini English Education Department, Language and Art Faculty, Surabaya State University. rrn.puspa@gmail.com Abstrak Penelitian ini bertujuan untuk mendeskripsikan penerapan model pembelajaran berbasis masalah untuk mengajar menulis teks surat lamaran kerja pada siswa kelas dua belas di SMKN 6 Surabaya dan untuk mendeskripsikan hasil menulis teks recount siswa selama penerapan model pembelajaran berbasis masalah untuk mengajar menulis teks surat lamaran kerja. Penelitian ini menggunakan penelitian deskriptif qualitative tanpa ada perhitungan statistik. Hasil penelitian ini menunjukkan bahwa model pembelajaran berbasis masalah sukses diterapkan di kelas dan model yang membantu baik guru dan siswa dalam proses belajar mengajar menulis teks surat lamaran kerja dalam konteks “content, organization, vocabulary, language use, and mechanics‟. Model pembelajaran berbasis masalahsebagai model pembelajaran mampu memotivasi siswa bergabung dalam proses pembelajaran di kelas dan mampu mengajak minat siswa untuk menulis. Kata Kunci: Menulis, Model Pembelajaran Berbasis Masalah, Teks Surat Lamaran Kerja. Abstract This study is conducted to describe the implementation of Problem-Based Learning in teaching writing application letter text to the twelfth graders of SMKN 6 Surabaya and the students writing result toward the implementation of Problem-Based Learning in teaching writing application letter text. This study used descriptive qualitative research without any statistical calculation. The result of this study showed that Problem-Based Learning was successfully implemented in class and it was helpful for both the teacher and the students in teaching and learning process of writing application letter text in terms of “content, organization, vocabulary, language use, and mechanics‟. Problem-Based Learning as a learning model could motivate the students involved in the learning process as well. Problem-Based Learning could encourage the students’ to write and engage the students’ willingness to write. Keywords:Writing, Problem-Based Learning, Application Letter.